THE IMPLEMENTATION OF E-FILING SYSTEM EFFECTS ON TAXPAYER COMPLIANCE IN SUBMITTING ANNUAL SPT AT DGT REGIONAL OFFICES, NORTH SUMATRA I - Sari, Ayu Kurnia; Sahputra, Hendra; Aulia, Aulia (Accounting and Business Journal, 2022)
The level of taxpayer compliance is still low in submitting the Annual SPT. There are still many taxpayers who have not implemented or utilized the use of the e-filing system. The formulation of the problem is whether the application of the E-filing system has an effect on taxpayer compliance in submitting annual tax returns at the North Sumatra DGT Regional Office. The results of this study are based on simple linear regression analysis, the variable of the application of the e-filing system has a positive and significant effect on taxpayer compliance in submitting the Annual Income Tax Return in the Regional Tax Office of North Sumatra I. This can be proven by the Adjusted R Square value obtained by 0.869, which means that the effect of implementing the e-filing system on taxpayer compliance is 86.90%. The remaining 13.1% is influenced by other factors other than the factors used in this study. based on the results of the t test, the significance value of the hypothesis is smaller than the level of significance, namely 0.000 < 0.05. This means that the implementation of the e-filing system has a significant effect on taxpayer compliance in the North Sumatra Regional Tax Office I.